Role of controlled radial expansion balloon bronchoplasty in benign subglottic and tracheal stenosis - Jeetendra Kumar Patra; Chinmaya Sundar Ray; Manoranjan Pattnaik; Subrat Kumar Behera (MGM Journal of Medical Sciences)
Background: Central airway obstruction can arise from both benign and malignant conditions, as well as from congenital or acquired causes. One common cause of acquired central airway obstruction is post-intubation subglottic and tracheal stenosis. Presentations can vary widely, from asymptomatic cases to symptoms such as difficulty clearing secretions and dyspnea on exertion due to airway narrowing. Critical tracheal or subglottic stenosis may present with stridor. Bronchoscopy is the primary diagnostic tool for assessing the type and severity of stenosis in the subglottic and tracheal regions. Controlled radial expansion (CRE) balloon bronchoplasty is a cost-effective procedure that can be performed either under sedation in a bronchoscopy suite or under general anesthesia in an operating room. This technique provides temporary relief and can be repeated, allowing time for more definitive or complex treatments. Materials and Methods: This case series study was conducted in the Department of Pulmonary Medicine in collaboration with the Department of Ear, Nose, and Throat at SCB Medical College and Hospital, Cuttack, Odisha, India, from January 2018 to July 2021. Six patients with subglottic and tracheal stenosis confirmed via fiber-optic bronchoscopy, all of whom had previously undergone tracheostomy, were included. Balloon bronchoplasty was performed using rigid laryngoscopy under general anesthesia with a CRE balloon (Boston Scientific), an Alliance-II integrated inflation device, a guide wire, and an Alliance inflation syringe. A follow-up fiber-optic bronchoscopy was conducted 1 month later. If an optimal tracheal diameter of 8–10 mm was not achieved, the patient underwent an additional CRE balloon bronchoplasty session. Results: This case series evaluated six patients with subglottic or tracheal stenosis. CRE balloon bronchoplasty was completed in three patients, with no recurrence of stenosis. However, the remaining three patients did not achieve an optimal tracheal lumen with CRE balloon bronchoplasty and were referred for tracheal reconstruction surgery. Discussion: CRE balloon bronchoplasty is an effective treatment for restoring optimal tracheal lumen in simple benign subglottic or tracheal stenosis cases. Patients with more complex stenosis should be considered for earlier referral to tracheal reconstruction surgery. Conclusion: CRE balloon bronchoplasty is a safe, straightforward, efficient, and repeatable procedure for relieving central airway obstruction due to benign subglottic and tracheal stenosis. It can serve as either a standalone treatment or an adjunct to other therapies for managing benign subglottic and tracheal stenosis.